139k views
1 vote
Combine like terms. What is a simpler form of the expression

-3(-4y + 3) + 7y

show your work

1 Answer

6 votes

First, distrbute -3 to both -4y and 3

-3(-4y) = 12y -> note that two negatives multiplied = one positive answer

-3(3) = -9 -> note that one negative and one positive = one negative answer

12y - 9 + 7y -> combine like terms

12y + 7y - 9

19y - 9 -> answer

Your answer is 19y - 9

hope this helps

~Crystal

User Subba
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.